2005
DOI: 10.1111/j.1529-8817.2005.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

ENVIRONMENTAL FACTORS CONTROLLING ALEXANDRIUM TAMARENSE (DINOPHYCEAE) GROWTH RATE DURING A RED TIDE EVENT IN THE ST. LAWRENCE ESTUARY (CANADA)1

Abstract: The dinoflagellate Alexandrium tamarense (Lebour) Balech 1985 is responsible for recurrent outbreaks of paralytic shellfish poisoning in the St. Lawrence Estuary. In July 1998, an A. tamarense red tide developed in the estuary with maximum cell concentrations reaching 2.3 Â 10 6 cells . L À 1 in brackish surface waters. To estimate the growth rate of these cells, surface water samples from different locations and days during the bloom were incubated for 5 to 9 days under in situ temperature and light condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 36 publications
7
34
1
Order By: Relevance
“…Consequently, during the incubation experiments, phosphate availability appeared to control the A. tamarense growth rate, while nitrate availability controlled the duration of the growth phase and, thus, the biomass yield. This result gives additional support to the hypothesis proposed by Fauchot et al (2005), which stipulates that A. tamarense growth may be limited by phosphate in the St. Lawrence estuary during red tide events. Combining the 2 data sets (1998 and 2000, see Fauchot et al 2005), we found a K s (phosphate concentration at which the A. tamarense growth rate is one half the maximum rate) of 0.26 µM.…”
Section: Alexandrium Tamarense Growth Rate and Nutrient Addition Expesupporting
confidence: 78%
See 4 more Smart Citations
“…Consequently, during the incubation experiments, phosphate availability appeared to control the A. tamarense growth rate, while nitrate availability controlled the duration of the growth phase and, thus, the biomass yield. This result gives additional support to the hypothesis proposed by Fauchot et al (2005), which stipulates that A. tamarense growth may be limited by phosphate in the St. Lawrence estuary during red tide events. Combining the 2 data sets (1998 and 2000, see Fauchot et al 2005), we found a K s (phosphate concentration at which the A. tamarense growth rate is one half the maximum rate) of 0.26 µM.…”
Section: Alexandrium Tamarense Growth Rate and Nutrient Addition Expesupporting
confidence: 78%
“…The difference in net growth rate between the phosphate and nitrate + phosphate addition experiments may result from the necessary adaptation of cellular metabolism to the sudden and simultaneous availability of nitrate and phosphate in the light. As previously hypothesized by Fauchot et al (2005), our results suggest that the growth rate of A. tamarense in the St. Lawrence estuary is controlled by phosphate availability, while the biomass reached during a bloom depends on nitrate availability and on the cells ability to perform vertical migrations.…”
Section: Nutrient Control Of Alexandrium Tamarense Growth Ratesupporting
confidence: 63%
See 3 more Smart Citations